Security at agricultural research stations - Austin, P.D. (1996)
Research stations are difficult to secure; yet security is especially important, because research results are lost if experimental crops, equipment and data are stolen. Security aims to protect life and proper-ty. Funding for security may seem wasted, but only one incident can cost more than investment in security. Security begins with good relations to the surrounding community. Security includes the establishment of a security force, appropriate station layout and fencing, and correct security management.